How Common Are Intentional GAAP Violations? Estimates from a Dynamic Model - ZAKOLYUKINA, ANASTASIA A. (Journal of Accounting Research, 2018)
ABSTRACT This paper uses data on detected misstatements—earnings restatements—and a dynamic model to estimate the extent of undetected misstatements that violate GAAP. The model features a CEO who can manipulate his firm's stock price by misstating earnings. I find the CEO's expected cost of misleading investors is low. The probability of detection over a five‐year horizon is 13.91%, and the average misstatement, if detected, results in an 8.53% loss in the CEO's retirement wealth. The low expected cost implies a high fraction of CEOs who misstate earnings at least once at 60%, with 2%–22% of CEOs starting to misstate earnings in each year 2003–2010, inflation in stock prices across CEOs who misstate earnings at 2.02%, and inflation in stock prices across all CEOs at 0.77%. Wealthier CEOs manipulate less, and the average misstatement is larger in smaller firms.